Structural properties of deposited ZnO thin films on flexible substrates at various substrate temperatures and RF power - Muhamad Suki, Nur Sa'adah; Herman, Sukreen Hana; Ani, Mohd Hanafi; Mahmood, Mohamad Rusop (Trans Tech Publications, Switzerland, 2012)
ZnO thin films were deposited on Teflon substrates by RF magnetron sputtering at different substrate temperature and different RF power. In this work, we investigated the dependence of the deposition rate and also the ZnO physical and electrical properties on the substrate temperature and RF power. It is observed that the deposition rate increased as the temperature and RF power increased. FE-SEM images confirmed that microstructure of the thin films consists of nanoparticles. XRD data confirmed that the ZnO thin films at various RF power and substrate temperature have (002) structure.